End of the century [videorecording (DVD)] - Castro, Lucio; Barberini, Juan; Pujol, Ramon, 1981-; Maestro, Mía (Cinema Guild, Inc., 2020)
Lucio Castro offers both a sun-soaked European travelogue and an epic, decades-spanning romance. When Ocho, a 30-something Argentine poet on vacation in Barcelona, spots Javi, a Spaniard from Berlin, the attraction is subtle but persistent. After a missed connection on the beach, a third chance encounter escalates to a seemingly random hookup. But are these two merely beautiful strangers in a foreign city, or are they part of each other's histories, and maybe even their destinies.